2021
DOI: 10.3390/en14092713
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Simulation of High-Speed Induction Motor

Abstract: In the drives of high-speed devices, such as a blood centrifuge, dynamic states also play an important role in terms of the time and quality of the tests performed. The article presents the application of modified equations resulting from the mathematical model of an induction motor to model dynamic phenomena during motor start-up, both with mains supply and with frequency start-up. The applied solution considers the phenomenon of current displacement in the rotor bar and the phenomenon of saturation. The comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Direct torque control of IM was employed in a simulation research that combined motor parameter-dependent and motor parameter-independent optimization approaches [8]. By simulating and duplicating the dynamic processes that occur during the first launch of high-speed IMs [9]. It has been shown that the created model has the capacity to precisely predict the characteristic of IMs by comparing the simulation and experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Direct torque control of IM was employed in a simulation research that combined motor parameter-dependent and motor parameter-independent optimization approaches [8]. By simulating and duplicating the dynamic processes that occur during the first launch of high-speed IMs [9]. It has been shown that the created model has the capacity to precisely predict the characteristic of IMs by comparing the simulation and experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Induction motors are the most suitable choice in different fields of application, from low to high power [1]. The use of variable speed asynchronous motor drives has been existent since the early 1960s.…”
Section: Introductionmentioning
confidence: 99%
“…Induction motors usually do not have the problem of a failed start. Research on starting induction motors is usually devoted to reducing the starting time in order to reduce the motor overheating [18][19][20] and reducing the starting current in order to reduce the load on the network [21][22][23].…”
Section: Introductionmentioning
confidence: 99%